Hydrothermal Synthesis of Nitrogen-Doped Carbon Dots from Mangosteen Peel: Structural, Optical and Antioxidant Properties - Rueangprat, Pongsiri; Watchasit, Sarayut; Sirion, Uthaiwan; Jaratjaroonphong, Jaray; Trakulsujaritchok, Thanida; Suksai, Chomchai (Burapha Science Journal, 2026)
Background and Objectives: Carbon dots are nanoscale materials primarily composed of carbon atoms. They can be easily synthesized using carbon-rich precursors. In recent years, natural materials have increasingly been used as precursors for the synthesis of carbon dots due to their abundance, low cost, and environmental friendliness. The eastern region of Thailand is one of the major mangosteen cultivation areas in the country. Each year, a large amount of mangosteen peel waste is generated from consumption and food processing activities. Therefore, this research aims to add value to this agricultural waste by utilizing mangosteen peel as a carbon source for the synthesis of nitrogen-doped carbon dots. In this study, nitrogen-doped carbon dots with different nitrogen ratios (MCN1 and MCN2) were synthesized from mangosteen peel using a hydrothermal method, with urea as the nitrogen precursor. The structural characteristics, optical properties, and antioxidant activities of the synthesized nanoparticles were systematically investigated and compared. Methodology: Nitrogen-doped carbon dots derived from mangosteen peel with different nitrogen ratios (MCN1 and MCN2) were synthesized using a hydrothermal method, with urea employed as the nitrogen source. The characterization of both nanoparticles was carried out using various analytical techniques for example ATR–FTIR , Raman spectrometry, SEM–EDX, HR-TEM, zeta potential, UV–visible spectrophotometry and fluorescence spectrophotometry. The antioxidant activities of MCN1 and MCN2 nanoparticles were evaluated using several standard assays, including the DPPH radical scavenging assay, the ABTS radical cation decolorization assay, the ferric reducing antioxidant power (FRAP) assay, and total phenolic content analysis. Main Results: In this study, carbon dot particles were synthesized from mangosteen peel via a hydrothermal method, with nitrogen atoms doped at different ratios (MCN1 and MCN2). The objective was to investigate the effect of nitrogen content on the properties of the resulting carbon dots. Structural characteristics and physicochemical properties of the prepared carbon dots were examined using spectroscopic techniques and related structural characterization methods. The results revealed that increasing the nitrogen content led to a higher number of defect sites within the carbon structure. In addition, a higher nitrogen concentration influenced the surface charge properties of the particles, resulting in a less negative surface charge compared with particles containing lower nitrogen content. This alteration in surface charge directly affected the antioxidant activity. The antioxidant evaluation demonstrated that MCN1 particles, which contained a lower nitrogen content than MCN2, exhibited significantly higher antioxidant activity. These findings indicate that the structural features of carbon dots and the nitrogen composition play a crucial role in determining their antioxidant performance. Conclusions: In this study, nitrogen-doped carbon dot particles were successfully synthesized from mangosteen peel via a hydrothermal method using different nitrogen doping ratios (MCN1 and MCN2). Structural characterization of the synthesized carbon dots using spectroscopic techniques confirmed that a higher nitrogen content resulted in an increased number of structural defect sites. This structural modification also led to a decrease in the negative surface charge of the particles. The change in surface charge was found to have a direct effect on antioxidant activity. Notably, MCN1 particles, which contained a lower nitrogen content than MCN2, exhibited higher antioxidant activity. Therefore, it can be concluded that MCN1 carbon dots possess properties suitable for applications in inhibiting oxidative reactions. Especially, MCN1 show strong potential for use in food packaging materials that require antioxidant functionality to reduce oxidative reactions during food storage. Such materials could contribute to extending the shelf life of food products, minimizing quality deterioration, and enhancing food safety for consumers. Furthermore, this approach represents a promising strategy for valorizing agricultural waste, such as mangosteen peel, by converting it into high-value functional materials with potential industrial and environmental benefits.